Impact of chromatin on HIV-1 latency: a multi-dimensional perspective - Joanna E. Jones; Chelsea E. Gunderson; Brian Wigdahl; Michael R. Nonnemacher (Epigenetics & Chromatin)
Abstract Human immunodeficiency virus type 1 (HIV-1) is a retrovirus that infects multiple immune cell types and integrates into host cell DNA termed provirus. Under antiretroviral control, provirus in cells is able to evade targeting by both host immune surveillance and antiretroviral drug regimens. Additionally, the provirus remains integrated for the life of the cell, and clonal expansion establishes a persistent reservoir. As host cells become quiescent following the acute stage of infection, the provirus also enters a latent state characterized by low levels of transcription and virion production. Proviral latency may last years or even decades, but stimuli such as immune activation, accumulation of viral proteins, and certain medications can trigger reactivation of proviral gene expression. Left untreated, this can lead to virema, development of pathogenic out comes, and even death as the immune system becomes weakened and dysregulated. Over the last few decades, the role of chromatin in both HIV-1 latency and reactivation has been characterized in-depth, and a number of host factors have been identified as key players in modifying the local (2D) chromatin environment of the provirus. Here, the impact of the 2D chromatin environment and its related factors are reviewed. Enzymes that catalyze the addition or removal of covalent groups from histone proteins, such as histone deacetylase complexes (HDACs) and methyltransferases (HMTs) are of particular interest, as they both alter the affinity of histones for proviral DNA and function to recruit other proteins that contribute to chromatin remodeling and gene expression from the provirus. More recently, advances in next-generation sequencing and imaging technology has enabled the study of how the higher-order (3D) chromatin environment relates to proviral latency, including the impacts of integration site and cell type. All together, these multi-dimensional factors regulate latency by influencing the degree of accessibility to the proviral DNA by transcription machinery. Finally, additional implications for therapeutics and functional studies are proposed and discussed.